2020
DOI: 10.1002/adem.202000037
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Mechanical Characterization of Square‐Celled TRIP Steel Honeycomb Structures Produced by Electron Beam Melting

Abstract: Material-and energy-saving lightweight constructions are of particular interest to the industry since decades, especially for vehicle and aircraft production. One of the ways of reducing the weight in components is to replace a solid matrix by periodically recurring cell or truss structure. Cellular materials such as metallic foams, truss, or honeycomb structures are characterized by high specific energy absorption and rigidness. Due to their high specific stiffness and compressive strength, square honeycomb s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Thus, both parameter sets resulted in a fine-grained microstructure of very similar appearance characterized by slightly elongated grains along the building direction. Based on these results and data from the literature [ 10 , 19 , 21 ], it is assumed that all other material states processed by PBF-EB in the present work exhibited similar, narrow grain size distribution and similar grain morphology.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Thus, both parameter sets resulted in a fine-grained microstructure of very similar appearance characterized by slightly elongated grains along the building direction. Based on these results and data from the literature [ 10 , 19 , 21 ], it is assumed that all other material states processed by PBF-EB in the present work exhibited similar, narrow grain size distribution and similar grain morphology.…”
Section: Resultssupporting
confidence: 66%
“…Alongside the elongated grains, the crack growth is accelerated whereas it is decelerated when cracks are growing perpendicular to the longitudinal axis of the grains. In contrast to the microstructure of AISI 316L, the austenitic steel considered in the present work only exhibits a slightly elongated grain shape as discussed in Section 3.1 and as shown previously [ 10 , 21 ]. Instead, an isotropic microstructure with almost equiaxed grains developed due to the cyclic heat treatment inherent to the PBF-EB-process.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Damage-tolerant alloys are often materials exhibiting deformation mechanisms such as TRIP (Transformation Induced Plasticity) or TWIP (TWinning Induced Plasticity) because their excellent work-hardening capacity drastically improve their resistance to strain localization. Some authors have recently reported the successful fabrication of TRIP [12,[15][16][17] or TWIP [13,14,18] steels by AM. For lightweight applications, Ti-alloys are good candidates due their good specific strength.…”
mentioning
confidence: 99%